Thematic Qur'anic Exegesis on the Essence of Allah: A Comparative Study of Ahl al-Sunnah wa al-Jama'ah, the Ash'ari School, and the Maturidi School - Tilome, Zaidan Bagus Hikmatiyar; Nurrohim, Ahmad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to analyze the understanding of verses related to the Essence of Allah (Dhat Allah) in the Qur'an through a thematic exegesis approach (tafsīr al-maudhū'i) and to compare the theological interpretations of three major Sunni schools: Salaf (Ahl al-Sunnah), Ash‘ariyah, and Maturidiyah. Methodology: This research employs a qualitative approach based on library research. The data are derived from classical and contemporary Qur’anic commentaries, theological works, and relevant academic journals. Thematic exegesis is applied by collecting, classifying, and analyzing Qur’anic verses concerning the divine attributes, followed by a comparative analysis of the interpretative methods used by the three theological schools. Results: The findings indicate that the Salaf school adopts a textual approach by accepting the verses as they appear without interpretation (tafwīḍ), while the Ash‘ariyah employ a mediating approach by applying ta’wīl to verses that may imply anthropomorphism. Meanwhile, the Maturidiyah demonstrate a stronger rational tendency by interpreting most of the ambiguous (khabariyyah) attributes to preserve the purity of monotheism (tawḥīd). Originality/Value: This study highlights that the differences among the three schools are methodological rather than ideological, reflecting the richness of Islamic intellectual tradition. It contributes to contemporary theological discourse by promoting a moderate and tolerant understanding of the mutashābihāt verses related to the Essence of Allah, particularly in responding to modern theological challenges.